The role of domestic animals in the epidemiology of human african trypanosomiasis in Ngorongoro conservation area, Tanzania. Issue 1 (December 2015) - Ruiz, Juan; Nyingilili, Hamisi; Mbata, Geofrey; Malele, Imna
Abstract Background Trypanosomiasis is a neglected tropical disease caused by the trypanosome parasite and transmitted by the tsetse fly vector. In Sub-saharan Africa, both the human and animal variants of the disease are a great obstacle towards agriculture, development, and health. In order to better understand and therefore combat Trypanosomiasis, characterizing disease hotspots across species is critical. Methods In this study, 193 samples from cattle, sheep, and goats were collected from eight sites. Samples were taken from animals belonging mostly to Maasai herdsmen in the Ngorongoro Crater Conservation Area (NCA) and analysed for the presence of trypanosomiasis infection using PCR techniques. Those that tested positive forT. brucei parasite were further tested using SRA LAMP technique to check forT. brucei rhodesiense, the human infective subspecies of parasite. Results Our study found a high incidence ofTrypanosoma brucei infections across species. Of animals tested, 47 % of cattle, 91.7 % of sheep, and 60.8 % of goats were infected. Most of the infections were of theT. brucei species. We also identified sheep and goats as carriers of theT. brucei rhodesiense subspecies, which causes acute human trypanosomiasis. Conclusions Together, these results point toward the need for stricter control strategies in the area to prevent disease outbreak.